in verlegenheit geraten. die befangenheit des menschen als anthropolischer leitfaden in hans lipps "die menschliche natur". - Kerckhoven, Guy van (Revista de Filosofía, 2001)
in his last work, the phenomenological philosopher hans lipps raises the cuestion of human nature. this nature can only be revealed by striking the concepcion of its very essence. this conception has to be found within the realm of the differenciating possibilities, in which human nature appears. one of these is the possibility of having affections. through his phenomenological analysis of the human embarrassment and its expresion, lipp calls into question the "psycho-physical nature" of man by showing its original embodiment. in his aurel kolnai`s analysis of repugnance and criticizes ludwing klages´theory of gestures. the human embarrassment and its expression is a striking example of the fundamental "befindlichkeit" of human being.